High-resolution Mass Spectrometry Study of Palm Jaggery Components with an Emphasis on Anti-microbial Properties (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The palmyra (Borassus flabellifer L.) is a member of the Arecaceae family. The unfermentedpalmyra tree sap, or neera, is used to make jaggery. Antimicrobials are substances that kill or inhibit thegrowth of harmful microorganisms like bacteria, viruses, fungi, and parasites. The study focuses on elucidatingthe antimicrobial properties of palm jaggery by analyzing the bioactive metabolites identified through High-Resolution Accurate Mass Spectrometry (HRMS). Methodology: The optimised sample of Palm jaggery wastested for metabolomics analysis. The High-Resolution Accurate Mass Spectrometry system instrument with themodel name Orbitrap Eclipse Tribrid Mass Spectrometer developed by Thermo Fisher Scientific was used forthe analysis of Palm jaggery sample. The raw data obtained from the mass analyser were performed throughdefault parameters of “Compound discoverer 3.3.2.31” using online databases. Result: Utilizing HRMS, wesuccessfully identified a diverse array of bioactive compounds and other secondary metabolites. This study hasidentified four key metabolites namely Diselane, Selenophosphate, Cadmium Sulfide, and Carnosol as havingnotable antimicrobial properties. The reported antimicrobial efficacy of these components was systematicallyevaluated and previous studies revealed significant antibacterial activity, particularly against both Gram-positiveand Gram-negative strains. Conclusion: Reported findings not only enhance the understanding of palm jaggery’sbiochemical profile but also highlight its significance as a source of antimicrobial agents, warranting furtherexploration for applications in food preservation and healthcare. This study contributes to the growing body ofknowledge regarding the functional properties of traditional foods and their role in promoting public health.